(untitled) (Perner’s Contacts, 2016)
The paper challenges business implications of published research outcomes that apply mathematical analysis of container movements processes for specific geographical regions. Based on extensive and structured literature review of empty container repositioning, the paper identifies a lack of integration from a holistic point of view. The research is supported by qualitative study based on semi-structured in depth interviews of key actors´ managers and its analysis. The research questions if repositioning management is primarily perceived as an issue of equipment movement optimization or as one of collaboration especially in the case of the mostly landlocked hinterland in Central and Eastern Europe (CEE). The research addresses the topic of inland repositioning management with a linkage to the Central and Eastern Europe (CEE) countries that is not considered by geographically framed research studies mainly focused on contestable European hinterlands.